Maternal Immunization Against Respiratory Syncytial Virus: An Updated WAidid Consensus Document on Evidence, Implementation, and Public Health Priorities - Susanna Esposito; Matteo Riccò; Bahaa Abu-Raya; Giancarlo Icardi; Vana Spoulou; David Greenberg; Oana Falup Pecurariu; Ivan Fan-Ngai Hung; Albert Osterhaus; Vittorio Sambri; Nicola Principi (Vaccines, 2026)
Background: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract disease and hospitalization in early infancy. The availability of maternal RSVpreF vaccination and long-acting infant monoclonal antibodies has created two effective but operationally distinct pathways for passive protection. Methods: This WAidid consensus document focuses on maternal RSV immunization within an integrated early infancy prevention strategy. A multidisciplinary Consensus Development Group reviewed evidence on infant RSV burden and seasonality, maternal vaccine efficacy and effectiveness, transplacental antibody transfer, long-acting monoclonal antibodies, implementation, equity, and economic considerations. Recommendations were developed using a modified Delphi process with a prespecified consensus threshold of at least 75% agreement. Results: Maternal vaccination can provide protection from birth when administered sufficiently before delivery, whereas direct infant monoclonal antibody prophylaxis provides rapid protection independent of maternal immune response and placental transfer. The relative value of the two approaches depends on gestational age, vaccination-to-delivery interval, infant risk, birth timing, local RSV circulation, antenatal care access, product availability, and cost. Post-pandemic disruption of RSV seasonality increases the importance of flexible strategies that protect infants born outside historically defined seasonal windows. Direct head-to-head evidence remains limited; therefore, policy decisions should integrate trial efficacy, emerging real-world effectiveness, implementation feasibility, and local epidemiology rather than assume universal superiority of one strategy. Conclusions: Maternal vaccination and infant monoclonal antibodies should be positioned within a coordinated prevention pathway. Maternal vaccination may serve as the principal strategy for appropriately timed pregnancies with reliable antenatal access, while infant monoclonal antibodies are particularly important when maternal vaccination is absent, too close to delivery, or potentially ineffective, or when the infant is preterm or otherwise at increased risk. Surveillance and locally adapted implementation are essential to maintain protection as RSV epidemiology evolves.